Guidance Note: Practical introduction to adaptive management - Global, DT (DT Global, 2022)
DT Global is proud to introduce our new Guidance Note: Practical Intro duction to Adaptive Management There is a growing consensus around ada ptive management as an effective (even necessary) approach when progra ms are tackling complex development problems. While there is no standa rd definition of adaptive management, there is general agreement that such programs need to routinely engage with and respond to program con text; constantly test what works in that context; and adjust approache s, plans, and activities based on continuous learning. However, there remains a more limited body of evidence about what this looks like in practice—the enabling conditions, systems, resourcing, skills, and att itudes to effectively operationalise adaptive management. There is als o limited guidance around when adaptive management is required, and to what extent—both critical and often overlooked considerations when pl anning for successful adaptive management. This Guidance Note draws to gether lessons and good practice in adaptive management from across DT Global’s diverse portfolio of donor-funded programs. It outlines our conceptual framework for adaptive management, with practical guidance on how it can be applied by our program teams. It is also designed to help our teams distinguish adaptive management from good (non adaptive ) project management, consider when adaptive management is most useful on a program, and how adaptive a program (or part of a program) shoul d be.